The universal role of adaptive transcription in health and disease - Lissek, Thomas (The FEBS journal, 2025)
In animals, adaptive transcription is a crucial mechanism to connect environmental stimulation to changes in gene expression and subsequent organism remodeling. Adaptive transcriptional programs involving molecules such as CREB, SRF, MEF2, FOS, and EGR1 are central to a wide variety of organism functions, including learning and memory, immune system plasticity, and muscle hypertrophy, and their activation increases cellular resilience and prevents various diseases. Yet, they also form the basis for many maladaptive processes and are involved in the progression of addiction, depression, cancer, cardiovascular disorders, autoimmune conditions, and metabolic dysfunction among others and are thus prime examples for mediating the adaptation-maladaptation dilemma. They are implicated in the therapeutic effects of major treatment modalities such as antidepressants and can have negative effects on treatment, for example, contributing to therapy resistance in cancer. This review examines the universal role of adaptive transcription as a mechanism for the induction of adaptive cell state transitions in health and disease and explores how many medical disorders can be conceptualized as caused by errors in cellular adaptation goals. It also considers the underlying principles in the basic structure of adaptive gene programs such as their division into a core and a directional program. Finally, it analyses how one might best reprogram cells via targeting of adaptive transcription in combination with complex stimulation patterns to leverage endogenous cellular reprogramming dynamics and achieve optimal health of the whole organism.
Veröffentlicht: 28 November 2024
Gesehen am 16.07.2025